Adsorption dynamics of tannin on deacetylated electrospun Konjac glucomannan fabric. Issue 14 (22nd March 2018) - Ryosuke, Sato; Yamaguchi, Gaku; Nagai, Daisuke; Maki, Yasuyuki; Yoshiba, Kazuto; Yamamoto, Takao; Chu, Benjamin; Dobashi, Toshiaki
Abstract : We demonstrate the adsorption dynamics of Konjac glucomannan electrospun nanofabrics consisting of an initial diffusion-limited stage and a late stoichiometric relaxation stage and show how to design efficient adsorption using the crossover time. Abstract : A nonwoven fabric of Konjac glucomannan (KGM) for the adsorption of tannin was fabricated by using electrospinning and then followed by deacetylation with alkaline solution. To analyze the adsorption dynamics of tannin, the time course of the adsorption of tannin on the nonwoven KGM fabric was measured by immersing the fabric in tannin solution at different concentrations of tannin and amounts of the fabric. The initial and late stages of the adsorption behavior could be expressed, respectively, by using a diffusion-limited equation and a stoichiometric equation. A discussion on the dependence of the control parameters on the adsorption behavior is presented. The results represent the first step to provide an effective adsorption procedure for tannin in the use of modified KGM fabric.